So , Inverse of
is
.
Explanation:
An inverse function is a function that "reverses" another function: if the function f applied to an input x gives a result of y, then applying its inverse function g to y gives the result x, and vice versa, i.e., f(x) = y if and only if g(y) = x. As an example, consider the real-valued function of a real variable given by f(x) = 5x − 7. In functional notation this inverse function would be given by,
![{\displaystyle g(y)={\frac {y+7}{5}}}](https://img.qammunity.org/2021/formulas/mathematics/high-school/a46z0r6fhrq6f2cmlp9tri640byb7jdja5.png)
With y = 5x − 7 we have that f(x) = y and g(y) = x. Here we have
![f(x) = (x-7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/b9c2rkd1y1gwmwh6byplswz4t8lkiodmdi.png)
![f(x) = (x-7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/b9c2rkd1y1gwmwh6byplswz4t8lkiodmdi.png)
⇒
![f(x) = (x-7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/b9c2rkd1y1gwmwh6byplswz4t8lkiodmdi.png)
⇒
![f(x) =1- (7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/t178jbrkjsgxl0v7itn5y6p1u3cuconfi2.png)
Let f(x) = y:
⇒
![f(x) =1- (7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/t178jbrkjsgxl0v7itn5y6p1u3cuconfi2.png)
⇒
![y = 1 - (7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/svif9vfduelemrc5bryflen1c4t7izzmij.png)
⇒
![y -1 = (-7)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/j32ljv0yu97wnip66fz4ps58uosb2vud1v.png)
⇒
![x = (-7)/(y-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5zr3wltfp0fnvzftdbm5qsjm3l25jr312z.png)
So , Inverse of
is
.